Population dynamic of the predator Doru luteipes Scudder on maize plants - Cruz, Ivan; C. Oliveira, Antônio (Pesquisa Agropecuaria Brasileira, 1997)
The predator Doru luteipes (Scudder) (Dermaptera: Forficulidae) has shown a great potential as a biological control agent against two key pests of maize, the fall armyworm Spodoptera frugiperda (Smith) and the corn earworm Helicoverpa zea (Boddie). This work was conducted with the objective of verifying the presence of the predator on maize field crop, during six years, with monthly planting time, in Sete Lagoas, MG, Brazil, at Embrapa-CNPMS. Weekly, 100 whorls of maize plants were shown, and the number of ovipositions nymphs and adults of the predator was recorded. The percentage of plants with at least one individual (nymph or adult) was also computed. The presence of the predator was generalized. The greatest occurrence was observed during the summer time, which is the best period for maize growth in the region. An average of 4.11 egg masses, 10.65 nymphs and 84.19 adults was observed for each 100 sampled plants. Plants with the insect were 42.8% on average, reaching in some planting dates the level of 95%. Along the year, a quadratic response between planting dates and the insect life stages was observed. However, when splitting the planting dates in two periods before and after the minimum point of adjusted curve, the relationship was linear for all stages.